A multicenter, randomized, double‐blind, placebo‐controlled trial to test efficacy and safety of magnetic resonance imaging‐based thrombolysis in wake‐up stroke (WAKE‐UP). Issue 6 (12th March 2013) - Thomalla, Götz; Fiebach, Jochen B.; Østergaard, Leif; Pedraza, Salvador; Thijs, Vincent; Nighoghossian, Norbert; Roy, Pascal; Muir, Keith W.; Ebinger, Martin; Cheng, Bastian; Galinovic, Ivana; Cho, Tae‐Hee; et al.
<x xml:space="preserve">Abstract</x> Rationale In about 20% of acute ischemic stroke patients stroke occurs during sleep. These patients are generally excluded from intravenous thrombolysis. MRI can identify patients within the time‐window for thrombolysis (≤4·5 h from symptom onset) by a mismatch between the acute ischemic lesion visible on diffusion weighted imaging (DWI) but not visible on fluid‐attenuated inversion recovery (FLAIR) imaging. Aims and hypothesis The study aims to test the efficacy and safety of MRI‐guided thrombolysis with tissue plasminogen activator (rtPA) in ischemic stroke patients with unknown time of symptom onset, e.g., waking up with stroke symptoms. We hypothesize that stroke patients with unknown time of symptom onset with a DWI‐FLAIR‐mismatch pattern on MRI will have improved outcome when treated with rtPA compared to placebo. Design WAKE‐UP is an investigator initiated, European, multicentre, randomized, double‐blind, placebo‐controlled clinical trial. Patients with unknown time of symptom onset who fulfil clinical inclusion criteria (disabling neurological deficit, no contraindications against thrombolysis) will be studied by MRI. Patients with MRI findings of a DWI‐FLAIR‐mismatch will be randomised to either treatment with rtPA or placebo. Study outcome The primary efficacy endpoint will be favourable outcome defined by modified Rankin Scale 0–1 at day 90. The primary safety outcome measures will be mortality and death or dependency defined by modified Rankin Scale 4–6 at 90 days. Discussion If positive, WAKE‐UP is expected to change clinical practice making effective and safe treatment available for a large group of acute stroke patients currently excluded from specific acute therapy.